Factors affecting the use of outpatient services among rural population in Sabah, Malaysia - Adilius Manual; Mohd Yusof Ibrahim; Ho Chong Mun; Norazah Mohd Suki (Universiti Putra Malaysia, 2024)
Introduction: Health outcomes in Sabah are generally below the national average and may be even worse in rural areas with limited health resources. Primary care plays a crucial role in facilitating appropriate referrals to secondary care through outpatient services. This study uses Andersen's behavioural model to assess outpatient healthcare utilisation in Nabawan, examining user characteristics and variables impacting service usage. Materials and methods: Guided face-to-face interviews were conducted between February and May 2019 in 25 villages, with 438 respondents randomly selected in the Nabawan district. Participants were asked if they had visited an outpatient facility in the past two weeks. Descriptive statistics were used to assess respondent characteristics, while multiple logistic regression analysis was employed to investigate the relationship between various factors and outpatient care usage. Results: From the total respondents, 17.8% (78) reported visiting an outpatient facility in the preceding two weeks. Those who reported moderate or mild health restrictions were eight times more likely to need outpatient treatment than those with no health limitations (AOR = 7.6, 95% CI = 1.990, 29.040). Additionally, individuals with one illness were three times more likely to use outpatient care (AOR = 2.630, 95% CI = 1.220, 5.660), while those with multiple illnesses were seven times more likely (AOR = 6.770, 95% CI = 2.680, 17.090). Conclusion: Individuals' belief in their own needs, including self-reported health restrictions and disease history, drives them to seek care. This belief may also affect their adherence to medical advice, treatment recommendations, and follow-up care. Malaysian Journal of Medicine and Health Sciences (2024) 20(6): 98-109. doi:10.47836/mjmhs20.6.15